PENERAPAN PRINSIP KESETARAAN GENDER DALAM DUNIA KERJA PERSPEKTIF UNDANG- UNDANG NOMOR 13 TAHUN 2003 - Nor, Ilhaminatun (Universitas Nurul Jadid, 2023)
This research aims to examine how Law No. 13 of 2003 year applies gender equality in the workplace. The main focus of this research is how the law is applied in terms of gender equality in various industries. The research method used is the Normative research method. Data was collected through articles, scientific journals, theses, Law Number 13 on labor, and Laws relating to Employment. Research shows that although awareness and implementation of gender equality principles have increased, there are still problems to effectively implement them in the workplace. As the government, companies, and society must continue to support gender equality in the workplace.